Poor response to tuberculosis treatment with regimens without rifampicin in immunosuppressed AIDS patients - O'Donnel,M.M. (2002)
A prospective study was conducted on 79 advanced immunosuppressed AIDS patients from 1997 to 1999, during which nine cases of tuberculosis (TB) were diagnosed. The main clinical and laboratory characteristics and the response to TB treatment were reviewed. The clinical manifestations of TB were: pulmonary (six cases), extrapulmonary (two cases) and disseminated (one case). These patients were being treated with highly active antiretroviral treatment (HAART) and were not responding. In three cases an optional regimen without rifampicin (RMP) was indicated to maintain HAART during TB treatment. A clinical response to TB treatment (disappearance of fever) was observed in 6/9 patients during a mean of 73 days (SD = 96). The three unresponsive patients were those treated without RMP. A switch to TB regimens containing RMP was proposed and successful. In our study, though it was limited by a small sample size, the response to TB regimens without rifampin was poor in immunossupressed patients failing HAART.